UTILIZATION OF HYDROGEN SULFIDE-CONTAINING REFINERY FLARE GASЕS - Jeхenov M.K.; Ismagilov F.R.; Akhmetov S.M.; Diarov M.; Bektay Y.K. (Academic Scientific Journal of Chemistry, 2020)
Modern oil refinery flare does not provide the beneficial use of discharged hydrocarbon gases and vapors, which does not allow to reduce the volume of hydrocarbon gas burned in flare candles and reduce atmospheric pollution. To ensure a stable and trouble-free operation of the flare plant and to increase the efficiency of waste gas utilization, their preliminary compression using mechanical or jet compressors and the construction of gas treatment plants are required. A low-cost method of utilizing hydrogen sulfide-containing refinery gas is proposed, including two-stage gas compression by a liquid-ring compressor using an alkanolamine aqueous solution as a working fluid in the first stage of compression, separation of the compressor of first stage compression to produce desulfurized gas, hydrocarbon condensate and an alkanolamine saturated hydrogen sulfide. In the second stage, the compression of the desulfurized gas is carried out by a liquid-ring compressor using a hydrocarbon absorbent as the working fluid, cooling and separation of the compress of the second stage of compression produce lean gas, water condensate and absorbate. The aqueous condensate is mixed with saturated hydrogen sulfide alkanolamine absorbent and taken out for regeneration, the hydrocarbon condensate is mixed with the absorbate to produce BFLH, and the lean gas is subjected to membrane separation to produce hydrogen and fuel gas. Application of the method can partially cover the needs of refineries in hydrogen by reducing its losses, as well as return gas and hydrocarbon fractions for processing or to the fuel network of the plant.